TEKSTUR LAKON DRAMA BANGSAWAN RAJA KECIL PRODUKSI SANGGAR TEATER MATAN PEKANBARU - Nazri, Muhammad (Universitas Lancang Kuning, 2019)
Bangsawan drama is a traditional Malay theater in Riau. The play presents about life around the kingdom, presented according to the custom and the rules that have been determined. The original Malay stories that made into Bangsawan drama performances are Hang Tuah Lima Bersaudara, Sultan Mahmud Mangkat Dijulang and Laksamana Bintan. The story of Raja Kecil was taken from the history of the founder of Siak Kingdom which is packed into very interesting form of theater to be studied. The object of this study focuses on the texture of the play in the performance of the Raja Kecil. This research uses Dramaturgy theory by using a descriptive qualitative approach method. The process of interviewing, observing, documenting are the ways that have been through to find out the play texture. Keywords: Bangsawan Drama, Play Texture, Matan Theater